Flow‐field‐assisted shaping of linear low‐density polyethylene/low‐entanglement ultra‐high molecular weight polyethylene blends with enhanced mechanical properties and thermal conductivity. Issue 3 (27th October 2022) - Zhang, Yu; Yan, Xiang; Ye, Chunlin; Tao, Gan; Zhang, Letian; Xing, Jinheng; Li, Wei; Wang, Jingdai; Yang, Yongrong
Abstract: Linear low‐density polyethylene (LLDPE) is reinforced with low‐entanglement ultra‐high molecular weight polyethylene (UHMWPE) and formed using different melt processing methods. The results show that the low‐entanglement UHMWPE has good compatibility with LLDPE within a low addition range, which significantly improves the crystallinity and long period of LLDPE/UHMWPE composites. Furthermore, the shish‐kebab structure of the composite material is more perfect after injection molding and hot drawing. Due to the optimized structure, the mechanical properties of the composite are greatly improved. After hot drawing, the Young's modulus and tensile strength of the composites are increased by 350% and 565% respectively. Simultaneously, after injection molding and hot stretching molding, the thermal conductivity of the material is increased by 138% and 711% respectively. The thermal conductivity of the materials can be significantly improved by hot drawing. The current study opens a new avenue for the preparation of bulk polymers using the LLDPE matrix with simultaneously enhanced thermal conductivity and mechanical properties, with great potential for applications in thermal management. © 2022 Society of Industrial Chemistry. Abstract : Linear low‐density polyethylene (LLDPE) is reinforced with low‐entanglement ultra‐high molecular weight polyethylene (UHMWPE) and formed using different melt processing methods.